PERKEMBANGAN REGULASI PERLINDUNGAN KONSUMEN DALAM TRANSAKSI E-COMMERCE DI INDONESIA DAN NEGARA-NEGARA ASEAN - Deky Paryadi (Faculty of Law - Tarumanagara University, 2017)
The development of increasingly advanced technology to make many changes in various fields. The existence of Internet technology is a positive impact for humans, especially in the field of trade, the evolution of information technology have created a new trend in the trading system, from conventional trade. Characteristics of e-commerce that is different from the conventional trade, making e-commerce as something that is new and has not been understood for some communities in Indonesia. Looking at the phenomenon of e-commerce business rapidly so it is important to put the consumer as a subject that is closely associated with e-commerce businesses. This study is a normative legal research of the Consumer Protection Act and the Commerce Act as a reference view of consumer protection in e-commerce trading. The results of this study found several factors that hinder the continuity of e-commerce in Indonesia, among others, public awareness, security of transactions, the limitations of internet banking facilities, culture or habit of Indonesian society are not entirely familiar with the use of internet in the trade, as well as resistance from providers e-commerce is not entirely lacks credibility and trustworthy. Therefore we need government intervention, such as more stringent oversight function, due to differences between the characteristics of e-commerce with a conventional trade.Keywords: E-commerce, Consumer Protection, Trade Act